Carbamazepine and carbamazepine-10, 11-epoxide therapeutic drug monitoring and biochemical and hematological evaluation in bipolar disorder outpatients (Research, Society and Development, 2021)
The objective of this study was to validate an analytical technique with HPLC-PDA for plasma measurement of carbamazepine (CBZ) and its metabolite carbamazepine-10, 11-epoxide (CBZ-E) for therapeutic monitoring (TM) of patients diagnosed with bipolar disorder (BD), as well as evaluating hematological and biochemical parameters of patients using CBZ. Sixteen patients registered with the Public Service of Psychiatry were selected. CBZ and CBZ-E measurements were performed with HPLC-PDA shimadzu LC-20 AT Prominence, under concentration gradient. Validation criteria: selectivity, linearity, precision, accuracy, recovery, stability. Hematological and biochemical tests were performed using conventional methods. As a result, it was obtained: accuracy >85% and precision